KOMPETISI DAN WORKSHOP METAVERSE UNTUK SMA/SMK DI JABODETABEK - Haris., M.TI, Darius Andana; Setiawan, Jerry; Cuang, Edgar Johan (Jurnal Bakti Masyarakat Indonesia, 2023)
The development of information technology makes it mandatory for the young generation in Indonesia to be digitaltechnology literate. Digital literacy, especially in the use of various technological devices, is not only the domain ofadults. The concept of the Metaverse has moved closer to reality thanks to recent technological advances. Within theMetaverse, individuals can engage in the digital environment in a more immersive and unified way. One of the keyelements of the Metaverse concept is interconnectedness, where multiple digital platforms and environments canconnect seamlessly, facilitating an individual's seamless movement from one experience to another. In line withtechnological developments, the interests of the younger generation in Indonesia need to be utilized. As a form ofeffort to address partners' concerns about the lack of young people interested in VR, this competition and workshopwas held. The Metaverse competition and workshop are community service activities carried out by the GameDevelopment Lab from the Faculty of Information Technology, Tarumanagara University (FTI UNTAR). The targetsof this activity are high school/vocational school students in the Jabodetabek area. This activity was carried out over2 days, where the first was an introduction and training on Metaverse content creation and the second day was aMetaverse competition. Each participant created Metaverse content and is assessed by a team of judges who comefrom partners who have collaborated, in this case OmniVR. Participants compete in groups consisting of 3 people. Atotal of 11 groups from 8 schools competed and have produced their own metaverse products. The winner has beendetermined and the PKM implementation is running smoothly. ABSTRAK: Perkembangan teknologi informasi menjadikan generasi muda di Indonesia wajib melek teknologi digital. Literasidigital, terutama dalam pemanfaatan berbagai perangkat teknologi, tidak hanya menjadi domain orang dewasa.Konsep Metaverse telah semakin mendekati realitas berkat kemajuan teknologi baru-baru ini. Di dalam Metaverse,individu dapat terlibat dalam lingkungan digital secara lebih mendalam dan menyatu. Salah satu elemen kunci darikonsep Metaverse adalah saling terhubung, di mana berbagai platform dan lingkungan digital dapat terhubungdengan mulus, memfasilitasi perpindahan individu dari satu pengalaman ke pengalaman lain tanpa hambatan.Sejalan dengan perkembangan teknologi, minat generasi muda di Indonesia perlu digunakan. Sebagai salah satubentuk upaya menangani keresahan mitra dengan kurangnya generasi muda yang tertarik kearah VR, diadakanlahkompetisi dan workshop ini. Kompetisi dan workshop Metaverse merupakan kegiatan pengabdian kepadamasyarakat yang dilaksanakan oleh Lab Game Development dari Fakultas Teknologi Informasi UniversitasTarumanagara (FTI UNTAR). Sasaran dari kegiatan tersebut yaitu siswa SMA/SMK di wilayah Jabodetabek.Kegiatan ini telah dilaksanakan dalam waktu 2 hari di mana pertama merupakan pengenalan dan pelatihanpembuatan konten Metaverse dan hari kedua adalah kompetisi Metaverse. Setiap peserta membuat kontenMetaverse dan dinilai oleh tim juri yang berasal dari mitra yang telah bekerja sama, dalam hal ini adalah OmniVR.Peserta berlomba dalam bentuk kelompok yang terdiri dari 3 orang. Sebanyak 11 kelompok dari 8 sekolah berlombadan telah menghasilkan produk metaversenya sendiri. Pemenang telah ditentukan dan pelaksanaan PKM berjalanlancar.